2020
DOI: 10.1002/slct.202003003
|View full text |Cite
|
Sign up to set email alerts
|

Curcuminoids versus Pyrazole‐Modified Analogues: Synthesis and Cytotoxicity against HepG2 Cancer Cell Line

Abstract: Twenty compounds including curcuminoids and their pyrazolemodified analogues were synthesized in a two-step reaction: (i) condensation between benzaldehyde derivatives and pentane-2,4-dione and (ii) pyrazole cyclization of the 1,3-diketone group in the resulting curcuminoids with hydrazine hydrate. The synthesized compounds were assayed for in vitro anticancer activity against HepG2 cancer cell line by determining their half-maximal inhibitory concentration (IC 50). Pyrazole curcuminoid (1 a, IC 50 = 1.53 � 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(24 citation statements)
references
References 42 publications
(130 reference statements)
0
20
0
Order By: Relevance
“…The published procedurewas used to carry out the synthetic procedure of curcuminoids (1-6) bearing various substituents on aromatic rings 12,13,18,19 (Figure 1). A mixture of boron oxide (10.0 mmol) and pentane-2,4-dione (10.0 mmol) in ethyl acetate (20.0 mL) was stirred at 70 • C for 1 h in a 100-mL two-neck round-bottom flask to yield the solution of acetylacetone-borate complex.…”
Section: Synthetic Procedures For Curcuminoids (1-6)mentioning
confidence: 99%
See 4 more Smart Citations
“…The published procedurewas used to carry out the synthetic procedure of curcuminoids (1-6) bearing various substituents on aromatic rings 12,13,18,19 (Figure 1). A mixture of boron oxide (10.0 mmol) and pentane-2,4-dione (10.0 mmol) in ethyl acetate (20.0 mL) was stirred at 70 • C for 1 h in a 100-mL two-neck round-bottom flask to yield the solution of acetylacetone-borate complex.…”
Section: Synthetic Procedures For Curcuminoids (1-6)mentioning
confidence: 99%
“…Curcumin (1), a constituent of turmeric powder derived from the rhizome of C. longa, is an attractive compound with broad-spectrum capacities including anti-oxidant 5 , anti-inflammatory 6 , and antitumour 7 activities. In particular, many studies reported that curcumin exhibited anti-cancer activity in a wide range of human cancers [8][9][10][11][12][13][14][15] . In addition, curcumin is pharmacologically safe as large quantities of curcumin, up to 10 g per day, can be consumed without inflicting toxicity 16 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations